Education And the Role of Women in Muslim Society - Tsagaraeva Olga Batyrbekovna; Rasulova Madina Askhatovna (Zien Journals, 2021)
The Islam and Muslim law have deeply influenced history of state development and legal regulations of a number of states, particularly the status of woman in society. The article examines the problem of legal position of women confessing Islam while religious prescriptions are more and more declining as a regulator of social relations
Keywords: Islam; women’s rights; social status; discrimination; Quran; Islamic feminism